Risk of stent failure in patients with diabetes treated with glucagon-like peptide-1 receptor agonists and dipeptidyl peptidase-4 inhibitors: A nationwide observational study. (1st May 2021) - Santos-Pardo, Irene; Lagerqvist, Bo; Ritsinger, Viveca; Witt, Nils; Norhammar, Anna; Nyström, Thomas
Abstract: Background: Incretins are a group of glucose-lowering drugs with favourable cardiovascular (CV) effects against neoatherosclerosis. Incretins' potential effect in stent failure is unknown. The aim of this study is to determine if incretin treatment decreases the risk of stent-thrombosis (ST), and/or in-stent restenosis (ISR) after percutaneous coronary intervention (PCI) with implanted drug-eluting stents (DES). Methods: Observational study including all diabetes patients who underwent PCI with DES in Sweden from 2007 to 2017. By merging 5 national registers, the information on patient characteristics, outcomes and drug dispenses was retrieved. Cox regression analysis with estimated hazard ratios (HRs) adjusted for confounders with 95% confidence intervals (CIs) was used to analyse for the occurrence of ST/ISR, and major adverse cardiovascular events (MACE). A subgroup analysis for the type of incretin treatment was performed. Results: In total 18, 505 diabetes patients (30% women) underwent PCI, and 32, 463 DES were implanted. Of those, 10% (3449 DES in 1943 patients) were treated with incretins. Median follow-up time was 995 days (Control Group) vs. 771 days (Incretin Group). No significant difference in the risk of ST/ISR was found neither for the main study group (HR:0.98 95% CI:0.80–1.19) nor for the subgroups. No reduction of the risk of MACE (HR:0.96 95% CI:0.88–1.06) was observed. There was a 26% lower risk for CV death in favour of incretin treated patients (HR:0.74 95% CI:0.57–0.95). Conclusion: In diabetes patients who underwent PCI incretin treatment was not associated with lower risk of stent failure, but with lower risk of CV death. Highlights: Patients with diabetes have a higher risk of in-stent restenosis and stent thrombosis. Potential beneficial effect of incretins in the risk stent failure following a coronary angioplasty. No lower risk of stent failure in patients with diabetes treated with incretins was found.